1986
DOI: 10.3109/13816818609004140
|View full text |Cite
|
Sign up to set email alerts
|

Choroideremia in interstitial deletion of the X chromosome

Abstract: An earlier reported family with a deletion of the proximal long arm of the X chromosome was reinvestigated with special attention to the presence of choroideremia. Two females were identified as carriers of choroideremia while a tapeto-retinal dystrophy was ascertained in a mentally retarded boy. RFLP analysis revealed that the interstitial deletion covered the locus DXYS1 and not DXS17. Chromosome studies indicated a deletion within the Xq21 area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…A similar approach to choroideremia was feasible because the locus for choroideremia has been mapped to Xq2l.1-Xq2l.2 by tight linkage to polymorphic DNA markers (11)(12)(13)(14)(15)(16), by the study of individuals with choroideremia who have large deletions of this region (17)(18)(19)(20)(21)(22)(23), and by the characterization oftwo women with choroideremia and de novo X;autosomal translocations (24)(25)(26). Recently, Cremers et al (27) isolated a candidate cDNA for the choroideremia gene that was disrupted in males with the disease by large [>40-kilobase (kb)] genomic deletions and in a female with the disease by an X;13 translocation.…”
mentioning
confidence: 99%
“…A similar approach to choroideremia was feasible because the locus for choroideremia has been mapped to Xq2l.1-Xq2l.2 by tight linkage to polymorphic DNA markers (11)(12)(13)(14)(15)(16), by the study of individuals with choroideremia who have large deletions of this region (17)(18)(19)(20)(21)(22)(23), and by the characterization oftwo women with choroideremia and de novo X;autosomal translocations (24)(25)(26). Recently, Cremers et al (27) isolated a candidate cDNA for the choroideremia gene that was disrupted in males with the disease by large [>40-kilobase (kb)] genomic deletions and in a female with the disease by an X;13 translocation.…”
mentioning
confidence: 99%
“…Five patients were diagnosed as having more rare, butt well-known hereditary diseases; 2 brothers suffered from autosomal dominant microcephaly with lacunar atrophy of the retina and choroid [13], 2 unrelated, mentally retarded boys with choroideremia had X chromosomal deletions [14,15]. Finally a 14 year old boy with a progressive hearing disorder and ataxia in addition to RP had a diagnosis of infantile Refsum disease confirmed by high blood concentration of phytanic acid.…”
Section: Resultsmentioning
confidence: 99%
“…In a study on 515 visually impaired Swedish children Lindstedt [4] calculated prevalences of tapeto-retinal degenerations as 1.5:100.000 in age group 0-7 years and 3.4:100.000 in age group [8][9][10][11][12][13][14][15][16][17][18][19][20]. Population studies including all age groups have reached figures between 5.0:100.000 and 21.0:100.000 [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, given the fact that up to 15% of mutations in the CHM gene are entire or partial gene deletions [20], it is not surprising that contiguous gene deletions on the X chromosome that include deletion of Xq21 may rarely cause syndromic cases of CHM. Reported cases have included patients with comorbidities such as mental and motor retardation, sensorineural deafness, cleft lip and palate, and other clinical phenotypes [23–27]. A 2011 study reported on a patient who presented with CHM, as well as dysplasia of the auricular system, patent ductus arteriosus and enamel hypoplasia [28].…”
Section: Introductionmentioning
confidence: 99%